The Influence of Work Discipline and Reward and Punishment on Employee Performance at PT United Equipment Indonesia with Job Satisfaction as a Mediating Variable - Sari, Julia Permata; Lahindah, Laura (Yayasan Riset dan Pengembangan Intelektual, 2025)
This study investigates the influence of work discipline and reward and punishment on employee performance at PT United Equipment Indonesia, with job satisfaction serving as a mediating variable. Employing a causal-comparative and associative research design, the study uses a quantitative explanatory approach. Data were collected through a structured questionnaire distributed to employees using simple random sampling, and analyzed using Structural Equation Modeling (SEM) with the Partial Least Squares (PLS) approach via SmartPLS software. The findings reveal that both work discipline and reward and punishment have a significant positive effect on job satisfaction and employee performance. Additionally, job satisfaction significantly contributes to enhancing employee performance. Mediation analysis confirms that job satisfaction plays a significant mediating role in the relationship between the independent variables and employee performance. These results highlight the importance of implementing effective disciplinary measures and balanced reward-punishment systems to foster employee satisfaction and improve overall organizational performance.